An unusual case of multiple skin abscesses caused by methicillin-resistant Staphylococcus aureus in a 6-year-old boy - Vinayaka, G; Vijaya Surya Kiran, K M; Amulya, V; R, Darshan (Indian Journal of Case Reports, 2024)
This report is a rare case of a 6-year-old child presenting with multiple skin abscesses resulting from a methicillin-resistant Staphylococcus aureus (MRSA) infection post blunt trauma to the pelvic region. Staphylococcus aureus poses challenges due to its antibiotic resistance. The child’s condition, marked by sepsis and extensive abscesses, prompted a multidisciplinary approach involving antibiotic therapy and surgical interventions. The MRSA strain exhibited resistance to various antibiotics, emphasizing the importance of individualized treatment as per the case. The case underlines the complexities of managing multi-site MRSA infections and emphasizes the significance of accurate diagnosis, appropriate antibiotic selection, and surgical intervention for successful outcomes.